Treatment of inguinal hernias Police Hospital Experience - Fernández, Alvaro; Payssé, Ignacio; Faruolo, Marisa; Kenny, Juan; Sgavaratti, Aldo; Silveira, Susana; Sánchez, Luis (Cirugía del Uruguay, 2005)
Repair of herniation is one of the most frequent surgical procedures performed by general surgeons and is probably the one which has most technical options. In current literature are described over a hundred of such procedures with various modifications whereupon we may conclude that there is no unique type of repair that has prevailed o ver and above the others as the ideal treatment. The rafe of complications and recurrences constitute the main quality criterion far herniorrhaphies. lt is not always possible to reproduce in University Hospitals the good results which are achieved in centers which specialize in the surgery of hernias. Surgeons have a different formative basis and general surgéons do not confine themselves exclusive/ y to this type of surgery.